إيديولوجيات صياغة الأخبار الصحفية في ظل الأنفوميديا الحديثة. (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ملخصحملت الصحافة الإلكترونية بعدا تقنيا وواقعا إعلاميا جديدا أكثر انفتاحا و تنوعا خاصة من الناحية التحريرية ، لذلك فقد سعينا من خلال دراستنا للبحث في أهم إيديولوجيات و أساليب صياغة الأخبار في الصحافة الإلكترونية و ما يميزها من ناحية الشكل و المضمون عن نظيراتها في الصحافة التقليدية .و ذلك من خلال استخدام منهجين تمثلا في منهج المسح و المقارن و بالاعتماد على أداتي الملاحظة و تحليل مضمون عينة من الصحف الإلكترونية الجزائرية تم اختيارها بطريقة قصدية خلال شهر ماي2020 ، و هو ما جعلنا نتوصل إلى مجموعة من النتائج أهمها : أن الأخبار الإلكترونية تحظى بنسق تحريري مميز ومتناسق مع البيئة التي تصدر بها . الكلمات المفتاحية: إيديولوجيات  ، الأخبار الصحفية ، الأنفوميديا الحديثة .                        Abstract :    The electronic press carried a technical dimension and a new media reality that is more open and diverse, especially in terms of editorial, so we have sought, through our study, to research the most important ideologies and methods of news formulation in the electronic press and what distinguishes it in terms of form and content from its counterparts in the traditional press ..And that is through the use of two methodologies represented in the survey and comparison approach and by relying on the two tools of observation and analysis of the content of a sample of Algerian electronic newspapers that were intentionally selected during the month of May 2020, which made us reach a set of results, the most important of which is: that electronic news has an editorial format Distinctive and consistent with the environment in which it is issued . Key words: Ideologies  , Press Releases , Modern Infomedia.